2021
DOI: 10.14712/23362936.2021.23
|View full text |Cite
|
Sign up to set email alerts
|

Short Review of Liposteroid: A Novel Targeted Glucocorticoid Preparation for Treatment of Autoimmune and Inflammatory Diseases

Abstract: This paper briefly reviews the safety and efficacy of liposteroid in different inflammatory and non-inflammatory diseases. Corticosteroids (CS) are the first-line therapy in many inflammatory and autoimmune disorders. Although highly efficacious, long-term use of CS is limited due to the occurrence of significant side effects. Liposteroid, which is a liposomal formulation of dexamethasone palmitate, possess more potent anti-inflammatory and immunosuppressive properties compared to dexamethasone sodium phosphat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…11,24,42,49,53,64 The dismal survival in the past has improved with early introduction of immunosuppressive therapy. 11,53,63,82 Intriguingly, the patients in this cohort demonstrated a remarkable response to GFD. The majority of patients were managed with GFD without any recurrence of their hemorrhage.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…11,24,42,49,53,64 The dismal survival in the past has improved with early introduction of immunosuppressive therapy. 11,53,63,82 Intriguingly, the patients in this cohort demonstrated a remarkable response to GFD. The majority of patients were managed with GFD without any recurrence of their hemorrhage.…”
Section: Discussionmentioning
confidence: 74%
“…Previous experience suggests that the treatment is often complicated by frequent recurrences and sometimes development of end‐stage lung disease requiring lung transplantation 11,24,42,49,53,64 . The dismal survival in the past has improved with early introduction of immunosuppressive therapy 11,53,63,82 . Intriguingly, the patients in this cohort demonstrated a remarkable response to GFD.…”
Section: Discussionmentioning
confidence: 90%
“…Approximately one-third of reported adult patients have required a second-line immunosuppressive agent to control their disease [ 86 ]. Unconventional therapies, such as liposteroid, leflunomide, and mesenchymal stem cell transplant, have also been tried [ 100 - 102 ]. In contrast, GFD alone was effective in controlling DAH in the majority of patients with LHS.…”
Section: Reviewmentioning
confidence: 99%
“…Liposteroid is a liposomal preparation of dexamethasone 21‐palmitate, which is more lipophilic than dexamethasone sodium phosphate (DSP). Liposteroid achieves a higher concentration in the inflamed tissue and demonstrates more potent anti‐inflammatory properties than DSP 75 . Several case reports and a retrospective study have reported the use of liposteroid in children with IPH 48,76,77 .…”
Section: Clinical Aspects In Iphmentioning
confidence: 99%
“…Liposteroid achieves a higher concentration in the inflamed tissue and demonstrates more potent anti-inflammatory properties than DSP. 75 Several case reports and a retrospective study have reported the use of liposteroid in children with IPH. 48,76,77 The liposteroid appears to be efficacious and associated with a better side-effect profile than conventional steroid therapy.…”
Section: Treatmentmentioning
confidence: 99%